Design and development of a cantilever triboelectric energy harvester - Muhammad Shazwan Iskandar Bin Mohd Shakirin (2023)
The major purpose of the thesis is to design and develop a cantilever triboelectric energy harvester (CTEH) that can operate at low frequency. This device well be develops based on the theory of triboelectric and energy harvesting.